2016
DOI: 10.1007/s10096-016-2669-x
|View full text |Cite
|
Sign up to set email alerts
|

Association of diverse bacterial communities in human bile samples with biliary tract disorders: a survey using culture and polymerase chain reaction-denaturing gradient gel electrophoresis methods

Abstract: Bacterial infection is considered a predisposing factor for disorders of the biliary tract. This study aimed to determine the diversity of bacterial communities in bile samples and their involvement in the occurrence of biliary tract diseases. A total of 102 bile samples were collected during endoscopic retrograde cholangiopancreatography (ERCP). Characterization of bacteria was done using culture and polymerase chain reaction-denaturing gradient gel electrophoresis (PCR-DGGE) methods. Antimicrobial susceptibi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
33
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(36 citation statements)
references
References 31 publications
2
33
1
Order By: Relevance
“…In Spain, the analysis of a total of 1429 E. coli isolates causing intra-abdominal infections in a surveillance study called SMART (Study for Monitoring Antimicrobial Resistance Trends) between 2016 and 2017 revealed that ciprofloxacin and amoxicillin-clavulanic acid presented resistance rates of 27.6% and 18.5%, respectively [36]. However, in Iran, the MDR pattern was detected in 95.5% of the E. coli recovered from bile, reporting different antimicrobial resistance rates in comparison with our results, mainly in the case of third generation cephalosporins (82% vs. 0%), carbapenems (≈70% vs. 0%), gentamicin (36.4% vs. 6.6%), and ciprofloxacin (45.5% vs. 13.3%), respectively [37].…”
Section: Discussioncontrasting
confidence: 44%
“…In Spain, the analysis of a total of 1429 E. coli isolates causing intra-abdominal infections in a surveillance study called SMART (Study for Monitoring Antimicrobial Resistance Trends) between 2016 and 2017 revealed that ciprofloxacin and amoxicillin-clavulanic acid presented resistance rates of 27.6% and 18.5%, respectively [36]. However, in Iran, the MDR pattern was detected in 95.5% of the E. coli recovered from bile, reporting different antimicrobial resistance rates in comparison with our results, mainly in the case of third generation cephalosporins (82% vs. 0%), carbapenems (≈70% vs. 0%), gentamicin (36.4% vs. 6.6%), and ciprofloxacin (45.5% vs. 13.3%), respectively [37].…”
Section: Discussioncontrasting
confidence: 44%
“…H. pylori and other species of Helicobacter can survive at the alkaline pH of the bile as they can be detected in bile sampled from biliary diseases including CCA [36, 37]. Most of the H. pylori and other bacteria in the bile are coccoid form that may reflect responses to bile acids [38].…”
Section: Survival Of H Pylori In the Bilementioning
confidence: 99%
“…Most of the H. pylori and other bacteria in the bile are coccoid form that may reflect responses to bile acids [38]. In addition, biofilm formation by the bacteria in the bile seems facilitate survival in the environment within the human biliary tract [36]. Interestingly, an increased abundance of H. pylori virulence genes, i.e.…”
Section: Survival Of H Pylori In the Bilementioning
confidence: 99%
“…Bacterial infection and abnormal bilirubin metabolism will cause calcium bilirubin to deposit and accumulate into nucleation in the biliary tract, resulting in the formation of stones, especially the formation of pigment stones is more thought to be caused by a bacterial infection. Through the study of people without biliary diseases, it has been proved that the biliary tract is sterile under normal conditions [24], while bacteria grow in the bile culture of almost all patients with choledocholithiasis. And all bile samples in this study were also detected by high-throughput sequencing.…”
Section: Discussionmentioning
confidence: 99%